Rehabilitation of hospitalised patients after hip arthroplasty to prevent chronic functional deficits - Sowa, Katarzyna; Kotwas, Artur; Antczak, Krzysztof; Zdziarski, Krzysztof; Knyszyńska, Anna; Karakiewicz, Beata (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2019)
Introduction Coxarthritis, in Poland, affects approximately 8 million people. Early physiotherapy determines the success of treatment. Aim The aim of the study was to analyse the effectiveness of rehabilitation process of patients undergoing hip surgery. Material and methods Medical documentation of 100 patients who have undergone surgery was analysed. Results The most common diagnosis in patients was coxarthritis. The BMI values of the patient’s differed significan¬tly depending on their place of residence. Patients started rehabilitation between day 1 and day 4 after the surgery. The verticalisation in 89% of pa-tients was carried out on day 1. Ninety-three patients decided to learn to walk with crutches. Conclusions 1. Primary coxarthritis is an indication to refer the patient to endoprosthesis. 2. In the course of rehabilitation, there is a progress of the patient’s functional level. 3. The rehabilitation process is not affected by the patient’s gender.